Recent applications of molecularly imprinted polymer sensors equipped with smartphones for detection of pesticide residues in environmental samples - Fareha Hilaluddin; Keat Khim Ong; Mohd Nor Faiz Norrrahim; Nor Laili-Azua Jamari; Siti Hasnawati Jamal; Siti Aminah Mohd Noor; Noor Azilah Mohd Kasim; Wan Md Zin Wan Yunus; Norli Abdullah; Mohd Junaedy Osman; Syed Mohd Shafiq Syed Ahmad (Arab Journal of Basic and Applied Sciences)
Environmental monitoring of pesticide residues has become increasingly crucial for ensuring food safety and environmental sustainability. Current demands are not met by traditional analytical tools, but the integration of smartphones, due to their small size, high accessibility, fast processing speed, and powerful imaging capacity, holds significant potential for on-site detection of pesticide residues. This review provides a comprehensive overview of the latest developments in the application of molecularly imprinted polymer (MIP) sensors equipped with smartphones for the detection of pesticide residues in environmental samples, covering the period from 2018 to 2024. The review encompasses recent advancements in MIP synthesis, sensor fabrication, and the incorporation of principles for improved signal precision with the integration of smartphones based on sensing signals (optical and electrochemical signals). Additionally, the diverse range of environmental samples were explored, including water, soil, and crops, where MIP sensors have demonstrated their efficacy in detecting pesticides. The potential for real-time monitoring and the challenges associated with deploying these sensors at lab scale are discussed. Overall, this review highlights the transformative impact of MIP sensors with smartphone-based detection in the field of pesticide residue analysis, paving the way for enhanced environmental monitoring practices.